Implementation of a Green Supply Chain in Increasing Competitive Advantage in the Manufacturing Industry - Suwanda (International Journal of Science and Society, 2024)
Green supply chains include strategies and practices that aim to reduce environmental impacts and increase resource efficiency throughout the production process. With global attention to sustainability, implementing green supply chains is considered a critical step in maintaining a balance between industrial growth and environmental conservation. This research aims to investigate the impact of implementing a green supply chain on increasing competitive advantage in the context of the manufacturing industry. This research uses a qualitative approach with descriptive methods. The results of this research show that implementing a green supply chain in the manufacturing industry can have a significant positive impact. By optimizing the use of natural resources and energy, reducing production waste, and involving suppliers who adhere to sustainable practices, companies can achieve high operational efficiency. Production cost savings obtained from green supply chain practices can increase a company's profitability, while a company image that cares about the environment can attract customers who increasingly prioritize sustainability. In addition, close engagement with suppliers and encouragement of innovation in production processes results in economic sustainability and flexibility that allows companies to respond more effectively to changing markets and customer needs.